Bis(1, 2, 4‐oxadiazolyl) Furoxan: A Promising Melt‐Castable Eutectic Material of Low Sensitivity. Issue 4 (30th January 2019) - Johnson, Eric C.; Bukowski, Eric J.; Sabatini, Jesse J.; Sausa, Rosario C.; Byrd, Edward F. C.; Garner, Melissa A.; Chavez, David E.
Abstract: A scalable synthesis of bis(1, 2, 4‐oxadiazoyl) furoxan, C6 H2 N6 O4, its physical properties, and its theoretical performance values are described. Previous attempts to synthesize this compound required expensive reagents, and/or time‐consuming synthesis processes and low overall yields. In addition to disclosing a streamlined synthesis of bis(1, 2, 4‐oxadiazolyl) furoxan, we report its molecular configuration and crystal structure, as well as its correct melting point. Bis(1, 2, 4‐oxadiazolyl) furoxan exhibits a very insensitive behavior to impact, friction, and electrostatic discharge, with a calculated detonation pressure 20 % higher than that of TNT. Given its physical properties and theoretical performance values, this material can be classified as a promising ingredient in the development of melt‐castable eutectic technology. Abstract : A melt‐castable eutectic : A scalable synthesis of bis(1, 2, 4‐oxadiazolyl) furoxan, C6 H2 N6 O4, its physical properties, and its theoretical performance values are described. This material displays a calculated detonation pressure 20 % higher than TNT, and is very insensitive to impact, friction, and electrostatic discharge. The material is classified as an insensitive explosive ingredient that could find application in melt‐castable eutectic formulations.